Pengembangan E-Mind Mapping Berbasis Digital dalam Pembelajaran Matematika Sekolah Dasar - Abdul Majid; Fauziah Kamaruddin (Lembaga Yasin AlSys, 2026)
Although the development of digital learning media has received attention in several previous studies, research that specifically discusses the use of digital-based E-Mind Mapping to improve elementary school students’ understanding of mathematical concepts remains limited. This study aims to develop and evaluate the effectiveness of digital-based E-Mind Mapping in mathematics learning in elementary school. This study employed a quantitative approach with an experimental design, involving 28 fifth-grade students of SDN 50 Bonto Panno, Pangkep Regency, who were selected through purposive sampling. Data were collected using learning outcome tests, student response questionnaires, and observation sheets, and were then analyzed using descriptive statistical techniques and the paired-sample t-test. The results showed that the students’ mean pretest score of 62.4 increased to 84.7 on the posttest. The paired-sample t-test results showed a t-value of 9.85 with significance (p) < 0.001, indicating a significant difference between learning outcomes before and after the use of digital-based E-Mind Mapping media. In addition, the N-Gain test result showed a value of 0.68, which fell into the moderate-to-high category. Students’ responses to the use of this media were also in the very positive category, with a percentage of 91.2%. These findings indicate that visual- and digital-based learning media are effective in improving students’ understanding of mathematical concepts. The conclusion of this study affirms the importance of integrating E-Mind Mapping into mathematics learning as a more interactive and meaningful learning innovation, while also providing theoretical and practical contributions to the development of digital-based mathematics learning in elementary schools.